SUPPLY CHAIN DESIGN - Noman, Raza (Journal of process management and new technologies, 2020)
In this study, the analysis will be given on “Investigating the role of Knowledge Management in the global supply chain”.  For the data, collection manufacturing firms is chosen from Pakistan. The method for data collection is secondary data collection. To achieve this, a systematic review is conducted based on qualitative content analysis. The contributions of KM were analyzed through a case study of the Pakistan Dairy company. Further, the case is analyzed by the supply chain process.
Keywords: Suppy Chain; Knowledge Management; Supply Chain Process; Organizational Firm; Management Systems